Polar Transportation Equipment - Five-Ton Truck with high Flotation Tires. - Thomas,M. W. (1975)
A 5-ton truck with 19.75 x 20, low-pressure, high flotation tires was tested in the continental United States and at McMurdo, Antarctica to determine its suitability as a cargo transporting vehicle in snow-covered polar regions. The tests indicated the vehicle was satisfactory when operated on well-constructed, hard-packed snow roads, but unsatisfactory for operation over deep, undisturbed, snow surfaces as well as over partially compacted surfaces such as snow trails processed by vehicle traffic.